Improvement to the physical quality and imbibition pattern in seeds of candeia (Eremanthus incanus (Less.) Less.) - Davide, Antonio Cláudio; Tonetti, Olívia Alvina Oliveira; Silva, Edvaldo Aparecido Amaral da [UNESP][ (Universidade Federal de Lavras (UFLA), 2011)
The objective of this work was to develop a methodology for seed processing and X-ray analysis and to study imbibition pattern in seeds of candeia (Eremanthus incanus). Seeds were gathered in 2001 and 2002 in Morro do Pilar and Lavras respectively, processed and stored in a cold chamber (5ºC/60%RH) until the start of experiments. In order to identify unfilled seeds, a protocol was developed for X-ray use combining radiation energy (Kv) and exposure time (seconds). For elimination of unfilled seeds, an experiment was conducted using a South Dakota seed blower whereby different opening settings and ventilation times were combined. Original seed lots and categorized lots following radiograph viewing were tested by germination tests, with seeds being cleansed in sodium hypochlorite and scattered over blotting paper in 'gerboxes' and then taken to germinators with alternating temperatures of 20º-30ºC and 10 hours of light, for up to 15 days. Imbibition curves were determined under the conditions 30ºC, 20º-30ºC/10 hours of light and 30º-20ºC/10 hours of light. The X-ray protocol that best allowed viewing of internal seed structures was 30Kv for 45 seconds. Seed separation using the blower setting at a 3.0 opening for 30 seconds raised the number of embryonic seeds to values exceeding 99%, also raising the germination rates as a consequence. The imbibition pattern is three-phased and the germination process is completed in 72 hours. Under alternate temperatures, primary root growth is favored.

Conduziu-se este trabalho, com os objetivos de desenvolver métodos de beneficiamento e análise de raios X, e estudar o padrão de embebição de sementes de candeia (Eremanthus incanus). As sementes foram colhidas em 2001 e 2002, respectivamente, em Morro do Pilar e Lavras, beneficiadas e guardadas em câmara fria (5ºC/60%UR) até o início dos experimentos. Para identificar sementes vazias, foi desenvolvido um protocolo utilizando raios X combinando potência de radiação e tempo de exposição. Para a eliminação das sementes vazias foi realizado um experimento utilizando soprador tipo South Dakota, combinando aberturas do aparelho e tempo de ventilação. Os lotes originais e as categorias encontradas pelas radiografias foram testadas por testes de germinação, no qual as sementes foram lavadas em hipoclorito de sódio e distribuídas sobre papel, em gerbox, levadas para germinadores com temperatura alternada 20-30ºC, com 10 horas de luz, por até 15 dias. Foram determinadas as curvas de embebição, nas condições de 30ºC, 20-30ºC/10 horas de luz e 30-20ºC/10 horas de luz. O protocolo de raios X que melhor permitiu a visualização das estruturas internas da semente foi 30Kv por 45 segundos. A separação das sementes no soprador na abertura 3,0 por 30 segundos elevou o número de sementes com embrião para valores superiores a 99%, tendo como consequência, a elevação das taxas de germinação. O padrão de embebição é trifásico e o processo de germinação se completa em 72 horas. Sob temperatura alternada, o crescimento da raiz primária é favorecido.
Melhoria da qualidade física e padrão de embebição de sementes de candeia (Eremanthus incanus (Less.) Less.)
Keywords: Sementes florestais; Teste de raios X; Soprador de sementes; Sementes vazias; Germinação; Forest seeds; X-ray test; Seed blower; Unfilled seeds; Germination